Leaf ultrastructure of firefly display trees - S., Norlela; A. J., Amirul Aiman; T., Noraini; B. S., Ismail (Malaysian Nature Society, 2020)
The leaf micromorphological study of four species of display trees, Sonneratia caseolaris, Barringtonia racemosa, Gluta renghas and Hibiscus tiliaceus, was conducted. The methodology involved in this study include fixation, dehydration, critical point drying and viewing under a scanning electron microscope. Results showed that all four species showed different leaf epidermal micromorphology. The glandular trichomes were only present on the epidermal surface of G. rengas, and armed trichomes on the leaf epidermal surface of H. tiliaceus. No trichomes were found on the leaf epidermal surfaces of S. caseolaris and B. racemosa. The presence of warts or nodules was only observed on the leaf epidermal surface of S. caseolaris. Further studies on the anatomical and phytochemical composition of these four species should be conducted to understand and identify the main reason for firefly attraction to these species.